2020
DOI: 10.1016/j.omtm.2020.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Engineering and In Vitro Selection of a Novel AAV3B Variant with High Hepatocyte Tropism and Reduced Seroreactivity

Abstract: Limitations to successful gene therapy with adeno-associated virus (AAV) can comprise pre-existing neutralizing antibodies to the vector capsid that can block cellular entry, or inefficient transduction of target cells that can lead to sub-optimal expression of the therapeutic transgene. Recombinant serotype 3 AAV (AAV3) is an emerging candidate for liver-directed gene therapy. In this study, we integrated rational design by using a combinatorial library derived from AAV3B capsids with directed evolution by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
0
18
0
Order By: Relevance
“… 76 Recently, several groups have been working on developing a new AAV capsid based on the AAV3B serotype. [77] , [78] , [79] One result of this endeavour has been the identification of AAVS3, a serotype now in phase I/II clinical trials for HemB and Fabry disease.…”
Section: Viral Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“… 76 Recently, several groups have been working on developing a new AAV capsid based on the AAV3B serotype. [77] , [78] , [79] One result of this endeavour has been the identification of AAVS3, a serotype now in phase I/II clinical trials for HemB and Fabry disease.…”
Section: Viral Vectorsmentioning
confidence: 99%
“…Since the first clinical trial using a AAV serotype 2 vector to express coagulation factor IX for HemB, several trials have been performed on different naturally occurring or synthetic serotypes, including AAV5, AAV8, AAVrh10, AAVS3, AAV-Spark100, and AAV-Spark200 for HemA and HemB, with varying results ( Table 1 ). [79] , [80] , [81] , [82] , [83] , [84] While sustained protein expression was achieved in some, in others clinical development was discontinued due to safety issues or insufficient efficacy, highlighting the importance of a proper selection of the serotype and expression cassettes. Anyway, these studies showed that long-term liver transduction using AAV is possible and have paved the way for the use of rAAVs in the treatment of IMLD.…”
Section: Viral Vectorsmentioning
confidence: 99%
“…However, many capsid properties are intrinsically coupled to one another and efforts to optimize or re-direct any single attribute often result in capsids that fail basic tests of functionality, such as capsid assembly and genome packaging. ML models can greatly reduce the burden of multi-property optimization through in silico screening of variants (28), ensuring that optimization toward one property does not break other desired functions (29,30), shifting the engineering burden away from experimental approaches (28). For instance, four supervised models can be trained to learn sequence-to-function maps between capsid sequences and their ability to (i) transduce the liver, (ii) bypass off-target organs, (iii) evade neutralization, and (iv) produce at high yield.…”
Section: Safe and Effective Treatment At Lower Dosesmentioning
confidence: 99%
“…For example, several clinical trials for hemophilia B have produced an array of data about AAV in humans, useful for improving hepatocyte tropism, transduction efficiency, and reducing immunogenicity [ 119 ]. Most of these studies have focused on engineering the AAV capsid, one of the major tropism determinants, through directed evolution, rational design, or a combination of both [ 120 122 ].…”
Section: Section Ii: Identification Of Liver-tropic Aav Vectorsmentioning
confidence: 99%
“…This approach involves the rational design of mutant libraries with targeted mutations in residues that are likely to affect capsid function during the screening process, thus maximizing the identification of mutants with desired features. A recent study combined rational design with directed evolution to select for liver-targeted AAV3B-derived variants [ 122 ]. The library design only allowed for randomization of residues in surface-exposed VRs while keeping the backbone sequence intact to maintain structural integrity.…”
Section: Section Ii: Identification Of Liver-tropic Aav Vectorsmentioning
confidence: 99%